2020
DOI: 10.1111/poms.13092
|View full text |Cite
|
Sign up to set email alerts
|

Do Optimization Models for Humanitarian Operations Need a Paradigm Shift?

Abstract: O ptimization approaches for planning and routing of humanitarian field operations have been studied intensively.Yet, their adoption in practice remains scant. This opinion paper argues that effectiveness increase realized by such approaches can be marginal due to triviality of planning problems, external constraints, and information losses. Cost increases, on the other hand, can be substantial. These include costs of implementation and use, data gathering, and mismatches with organizational cultures. Though s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…The main limitation of the proposed approach is relatively long computing time, as a result its use in online mode is suitable only for cases with few delivery points. However, as the previous study has shown, the typical conditions for planning and routing of disaster relief mission include a small number of destinations per trip [9].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The main limitation of the proposed approach is relatively long computing time, as a result its use in online mode is suitable only for cases with few delivery points. However, as the previous study has shown, the typical conditions for planning and routing of disaster relief mission include a small number of destinations per trip [9].…”
Section: Discussionmentioning
confidence: 91%
“…Constraints ( 2)-( 11) describe the relationship between routes (represented by the variables x k i;j ) and the delivery schedule (variables y k i and s k ). They provide, among others, that it is not possible to take off several UAVs from the base at the same time ( 4), a recipient cannot by simultaneously served by several UAVs (6), deliveries are made in accordance with the adopted route ( 7), (8), it guarantees closed loops of the routes (9). Constraints ( 12)-( 22), link UAV routes (x k i;j ) to the amounts of delivered goods (variables c k i ).…”
Section: Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the complexity of the FDP, organizations such as MSI have good reason to prefer simple policies, the main one being that they fit with the prevailing decentralized decision‐making culture. Another is that advanced algorithms push up the costs of implementation, roll‐out, and training (De Vries and Van Wassenhove 2020). Organizations also value flexibility, that is, policies that simply recommend a frequency and leave the teams to decide on day‐to‐day planning.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Yet, there are considerations other than objectives. In the context of humanitarian logistics, De Vries and Van Wassenhove [54] find, “using richer objective functions may lead to more effective decisions but can also be more expensive due to software requirements, training, and data gathering.” Transportation science researchers need to find the balance that best serves their stakeholders. Finding this balance means working with stakeholders to identify their requirements and develop models that can account for these.…”
Section: Natural Environmentmentioning
confidence: 99%